Comparing the Real-World Effectiveness of Competing Colonoscopy Preparations: Results of a Prospective Trial. (February 2019) - Gu, Phillip; Lew, Daniel; Oh, Sun Jung; Vipani, Aarshi; Ko, Jeffrey; Hsu, Kevin; Mirakhor, Ebrahim; Pattisapu, Varun; Bullen, Tia; Fuller, Garth; Spiegel, Brennan M.R.; Almario, Christopher V.
Abstract : OBJECTIVES: National societies provide little guidance regarding which colonoscopy bowel preps are best tolerated and most effective; this reflects a lack of comparative effectiveness studies that directly evaluate the available preps in a "real-world" setting. To address this gap, we conducted a prospective, commercially unfunded comparative effectiveness study of currently available bowel preps and measured their impact on bowel cleansing. METHODS: We included patients aged ≥18 years, who presented for an outpatient colonoscopy at a large medical center serving more than 70 academic and community-based endoscopists who are free to prescribe the bowel prep of their choice. The primary outcome was bowel cleansing quality as measured by the Boston Bowel Preparation Scale. We performed regression models with random effects on the outcomes to adjust for confounding. RESULTS: Approximately 4, 339 colonoscopies were performed by 75 endoscopists. Magnesium citrate, MiraLAX with Gatorade, MoviPrep, OsmoPrep, Prepopik/Clenpiq, and Suprep all had significantly higher prep tolerability compared with GoLYTELY (all P < 0.05). For bowel cleansing, Suprep (7.28 ± 1.66; P < 0.001), MoviPrep (7.11 ± 1.62; P = 0.004), and MiraLAX with Gatorade (7.09 ± 1.64; P < 0.001) had higher total Boston Bowel Preparation Scale scores compared with GoLYTELY (6.67 ± 1.87); there were no significant differences among the remaining preps. Split-prep dosing was associated with better cleansing; however, men, opioid and tricyclic antidepressent users, and patients with diabetes and cirrhosis had worse cleansing (all P < 0.05). CONCLUSIONS: In this prospective, real-world comparative effectiveness study of available bowel preps, we found that MiraLAX with Gatorade, MoviPrep, and Suprep were prospectively associated with superior tolerability and bowel cleansing.